2022
DOI: 10.1088/1755-1315/1111/1/012077
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Fuel Station Accidents: The Importance of Community Involvement

Abstract: From 2016-2018 there were 120 fuel station accidents in Indonesia. Fuel station accidents may harm not only workers but also the public. Major accidents in fuel stations have caused multiple fatalities and injuries. Various research regarding fuel stations has been done, but research on the role of the community in preventing fuel station accidents is limited. Therefore, studying the cause and effect of fuel station accidents is essential. The study aims to collect accident information and determine the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although tanker unloading was identified as the activity with most significant risk factor [20], the frequency of this activity is much less than fuel dispensing, i.e., filling fuel to consumer vehicles. In addition, fuel dispensing activity involves interaction between gas station workers and the consumer driving the vehicles, for which unsafe behaviors often occur and need to be controlled [2].…”
Section: Gas Station Accident Contributing Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although tanker unloading was identified as the activity with most significant risk factor [20], the frequency of this activity is much less than fuel dispensing, i.e., filling fuel to consumer vehicles. In addition, fuel dispensing activity involves interaction between gas station workers and the consumer driving the vehicles, for which unsafe behaviors often occur and need to be controlled [2].…”
Section: Gas Station Accident Contributing Factorsmentioning
confidence: 99%
“…Moreover, a safety climate assessment in gas stations in Indonesia using the NOSACQ-50 questionnaire in West Java Region, Indonesia, showed that personal risk-taking behavior remains an issue to be resolved [14]. Another aspect specific to gas station safety is the involvement of the community in building safety awareness, since gas stations are usually located close to community dwellings [2].…”
Section: Safety Climate Studies In Gas Stationsmentioning
confidence: 99%
See 2 more Smart Citations
“…By taking all necessary precautions, we can help to reduce the risk of accidents at gas stations and keep ourselves and others safe [39].…”
Section: Potential Hazardsmentioning
confidence: 99%